ICT for promoting human development and protecting the environment : 6th IFIP World Information Technology Forum, WITFOR 2016, San José, Costa Rica, September 12-14, 2016, Proceedings /: 6th IFIP World Information Technology Forum, WITFOR 2016, San José, Costa Rica, September 12-14, 2016, Proceedings. (2016) - Unknown
No abstract available